Relocation of Maternal–Fetal Medicine Specialists in the United States - Rayburn, William F.; Perez, Jose M.; Xierali, Imam M. (American Journal of Perinatology, 2019)
Objective To examine patterns in relocation of maternal–fetal medicine (MFM) specialists during the recent 10 years.Study Design This descriptive study analyzed the migration of MFM specialists between 2006 and 2016 based on county locations. Year-to-year comparisons of physicians in active clinical practice were performed. Demographic and county characteristics were gathered from three data resources. A multivariable logistic regression model was used to identify factors associated with relocation.Results An average of 7.4% (5.5–10.8%) of all 1,104 (1,103–1,115) MFM specialists moved per year. Approximately one in three (36%) relocated during the 10 years, usually once or twice. The likelihood of relocation was higher if the physician was younger, especially under 40 years compared with those aged 60 years and older (odds ratio [OR] = 2.08; 95% confidence interval [CI]: 1.36–3.19). No differences were noted based on gender and race/ethnicity. Physicians in independent group practices were more inclined to relocate, especially when compared with those in a solo or two-physician practice (OR = 0.38; 95% CI: 0.27–0.54). Relocations were primarily between urban counties (95.9%) and showed a significant regional pattern.Conclusion Approximately one in three MFM specialists relocated in the past 10 years, mostly between urban counties and especially in independent group practices.
Keywords: distribution; maternal–fetal medicine specialists; migration; relocation